Rancang Bangun Media Pembelajaran Interaktif Mata Pelajaran Pemrograman dan Aplikasi Mikrokontroler - Umar Hamdan; Ilmiyati Rahmy Jasril (MASALIQ, 2025)
Education plays a crucial role in developing students’ potential, and with the rapid advancement of information and communication technology, innovation in learning media has become increasingly relevant in creating practical, engaging, and interactive learning experiences. This study aims to design and develop interactive learning media using Adobe Animate for the subject "Microcontroller Programming and Applications" for Grade XI students majoring in Audio Video Engineering at SMK Negeri 1 Sumatera Barat. The method employed is Research and Development (R&D) using the 4-D development model, which includes the stages of Define, Design, Develop, and Disseminate. Validation was conducted by two subject matter experts, resulting in a validity score of 94.7%, and by a media expert with an average validity score of 100%, both categorized as “Highly Valid.” A practicality test involving 15 students showed a practicality level of 96%, classified as “Highly Practical.” The results of this study indicate that the developed interactive learning media is suitable and effective for use in the learning process and supports the achievement of student competencies in microcontroller-related material.